Tales of Indigenous Students in Central Kalimantan: Narrative Inquiry on English Learning Experience - Muhammad Subhan Fikri; Novika Amalia; Richard Ferry Nugraha; Rezqan Noor Farid (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2025)
Learning experience is an integral factor of language perception construction. Having a positive experience is more likely to construct a positive perception of the language. English students in Universitas Palangka Raya are indigenous people in Kalimantan who comes from different parts of Central Kalimantan. These students experienced learning processes that are highly influenced by the condition of the school, the teachers, and their environment. This study aims to understand the indigenous students learning experiences in Central Kalimantan to explore the construction process of their perception of English throughout these experiences. This study involved five English education students. We conducted a conversational interview to collect the participants’ stories of their learning experienced. We found that all of the participants chose English education study program because they were interested in the language. These interests are built through their language learning experience. Even if the students reported school and classroom environments as the biggest factor of their negative experience of English, they still found interest in English through usage in their lives such as hobbies and communication.